Antagonistic Activity of Extremophilic Bacteria Against Phytopathogens in Agricultural Crops - Lyudmila K. Asyakina; Yuliya R. Serazetdinova; Anna S. Frolova; Natalya V. Fotina; Olga A. Neverova; Andrey N. Petrov (Техника и технология пищевых производств)
Wheat is a vital agricultural crop whose phytopathogens include fungi of the genera Fusarium and Alternaria. Synthetic pesticides, which are used to combat them, have a negative impact on the environment. Therefore, there is a need for developing safe and effective biopesticides. We aimed to create a consortium of extremophilic microorganisms isolated from natural sources to protect wheat from the diseases caused by Alternaria and Fusarium fungi. Ten isolates of extremophilic microorganisms were tested for their antimicrobial activity against Escherichia coli and their antagonistic activity against phytopathogens. Based on the results, we developed microbial consortia and evaluated their effectiveness in protecting wheat from phytopathogens. Five of the strains under study showed the highest activity, three of which were biocompatible, namely Leclercia sp., Sphingomonas paucimobilis, and Lactobacillus plantarum. Four consortia were created from these microorganisms, of which consortium B (with a 2:1:1 ratio of the strains, respectively) proved the most effective. In particular, it increased the area free from the phytopathogen by 4.2% compared to the average values of its individual microorganisms. Also, the consortium had a phytostimulating effect on wheat seedlings (germination of 73.2–99.6%) and protected the seeds infected with phytopathogens from morphometric changes. The resulting consortium can be used as a biopesticide since it is highly effective in protecting wheat from Alternaria and Fusarium pathogens.